Quadrupole wiggler for a collinear wakefield accelerator - M. Qian; M. Kasa; J. Xu; S. Doran; S. Lee; S. Sorsher; N. Strelnikov; E. Trakhtenberg; A. Zholents (Physical Review Accelerators and Beams)
A quadrupole wiggler consisting of a row of alternating-polarity permanent magnet-excited quadrupoles is used in a collinear wakefield accelerator under development at Argonne National Laboratory. Fine translational and angular adjustment mechanisms are implemented in all quadrupoles to obtain a better than 1-μm precision in the alignment of quadrupole wiggler assemblies. The quadrupole’s magnetic and mechanical designs are described. Two wiggler prototypes were fabricated, aligned, and characterized performing pulsed wire magnetic measurements. The sensitivity of the quadrupole wiggler alignment to the ambient temperature was measured.